Color Stability of Different Aesthetic Archwires after Immersion into Different Types of Mouthwashes(An In Vitro Study) - Hussein, Lubna M; Ghaib, Nidhal H (Journal of Baghdad College of Dentistry, 2017)
Background: Because of the demands for aesthetic orthodontic appliances have increased, aesthetic archwires have been widely used to meet patient's aesthetic needs. The color stability of aesthetic archwires is clinically important, any staining or discoloration will affect patient’s acceptance and satisfaction. This study was designed to evaluate the color stability of different types of aesthetic archwires after immersion into different types of mouth washes.Materials and methods: Four brands of nickel titanium coated aesthetic arch wires: Epoxy coated (Orthotechnology and G&H) and Teflon coated (Dany and Hubit) were evaluated after 1 week, 3 weeks and 6 weeks of immersion into two types of mouthwashes (Listerine with alcohol and Listerine without alcohol). Color change measurements were performed by using spectrophotometer VITA Easyshade Compact according to the commission Internationale de I’Eclairage L*a*b* color space system.Results: The results of this study showed that there were highly significant differences in color change values among all brands of aesthetic archwires at various immersion media. On the other hand, a significant difference was found between Dany and Orthotechnology aesthetic archwires at 1 week immersion in distilled water. Listerine with alcohol mouthwash produced more color changes of aesthetic archwires and color change value increases with the time of immersion.Conclusions: All brands of aesthetic archwires showed different degrees of color changes but most of these changes were not visible or clinically acceptable.